The study of connotation dožam Narges( The sad narcissus) in the Prologue of Rostam and Esfandiar - Ghodsieh Rezvanian; Reza Sattari; Maryam Ghorbanian (مطالعات زبانی و بلاغی)
Connotation or the indirect expression has been of crucial significance regarding literary criticism and rhetorical studies and aesthetics; so that, to be thoroughly perceived, needs an intense consideration beyond the lexical levels or verses and sentences, and what should be studied are the structure and the whole context of the work and the minor and the main elements of a work concerning the main constituent context. In this structural study, the narrative element has an important role; and only by applying a minute research on the components of the narrative structure and the correlation of these components with themselves and with the whole text in several aspects like connotation, an appropriate result could be achieved. Some of these above-mentioned constituent components and elements of the text are considered as lexical and syntactical layers (linguistic field), image: simile, metaphor, and allegory (rhetorical field), and drama (dramatic field) that are engaging in creating implemented meaning.Although the connotation is observed in different layers in Ferdowsi's poetry, insisting on the vocabulary and semantic layers this study has investigated the connotative meaning of Narges dožam (the sad narcissus) in the introduction of the Rostam and Esfandiar story finally had demonstrated this of eyes, crown, and drunkeness has three implicit meanings and the obtained results illustrate the consistency of the narrative context.